The effect of a 90-min soccer match and fatigue on eccentric hamstring strength: implications for hamstring injury risk - Kakavas, G.; Kekelekis, A. (British Journal of Sports Medicine, 2021)
Background Hamstring injury (HI) is the most prevalent muscle injury in both amateur (van Beijsterveldt et al., 2015) and professional (Ekstrand et al., 2011; Hawkins et al., 2001) soccer (football) players. Worryingly, the annual incidence of HI increased by 2.4% annually between 2010 and 2014 (Ekstrand et al., 2016)